2017
DOI: 10.1080/10942912.2017.1328439
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and structural properties of starches from different Indian wheat cultivars and their relationships

Abstract: The structural, pasting, and dynamic rheological properties of starches isolated from six Indian wheat (Triticum aestivum L.) cultivars were evaluated. The amylose content of starches ranged between 18.35-20.58%; subsequently, these were normal-type starches. The light transmittance of gelatinized starch pastes decreased with increase in storage periods at 4°C. Scanning electron micrographs revealed bimodal size distribution of starch granules, with smaller B-and larger A-type. X-ray diffraction (XRD) pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 36 publications
4
26
0
1
Order By: Relevance
“…4 769.5, and 567.4-584.7 cm −1 are related to the vibrations of anhydroglucose ring stretching. Similar results were reported by Brij et al [49] for wheat starch.…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 81%
“…4 769.5, and 567.4-584.7 cm −1 are related to the vibrations of anhydroglucose ring stretching. Similar results were reported by Brij et al [49] for wheat starch.…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 81%
“…Absorbance ratios of 1047/1022 cm −1 for the waxy, normal, and high-amylose starches were 0.631, 0.590, and 0.533, respectively, suggesting that the amount of short-range ordered structure decreased as the amylose content increased. This result was consistent with corn and wheat starches as previously reported by Chen et al (2019) and Karwasra et al (2017). Amylose molecules can entangle within the crystalline regions of amylopectin and interfere with the formation of double helices between branch chains of amylopectin molecules (Chen et al, 2019).…”
Section: Short-range Ordered Structuresupporting
confidence: 92%
“…The different sizes of the starch granules might be attributed to their different time of formation during grain development (Xie et al, 2008). Karwasra et al, (2017) observed that wheat contains generally bimodal size distribution of starch granule populations and has two types of size groups e.g. small granules (below 10-14 µm), large granules (above 10-14 µm to 36 µm) and the larger A-type wheat starch granules were generally disc like or lenticular while the smaller B-type granules were spherical and somewhat polygonal in shape.…”
Section: Study Of Starch By Sem Analysismentioning
confidence: 99%